Biodiversity: Concepts, patterns, trends, and perspectives - Díaz, Sandra Myrna (2022)
Biodiversity, a term now widely employed in science, policy, and wider society, has a burgeoning associated literature. We synthesize aspects of this literature, focusing on several key concepts, debates, patterns, trends, and drivers. We review the history of the term and the multiple dimensions and values of biodiversity, and we explore what is known and not known about global patterns of biodiversity. We then review changes in biodiversity from early human times to the modern era, examining rates of extinction and direct drivers of biodiversity change and also highlighting some less-well-studied drivers. Finally, we turn attention to the indirect drivers of global biodiversity loss, notably humanity's increasing global consumption footprint, and explore what might be required to reverse the ongoing decline in the fabric of life on Earth.